Popular Participation: Why do People Participate in Amateur Theatre? - Sigurðardóttir, Gerður Halldóra (Nordic Theatre Studies, 2018)
There are about sixty amateur theatre companies in Iceland. Hundreds of people every year participate in various theatrical activities, from staging large and intricate productions to smaller and more intimate readings and programs, attending workshops and seminars, writing plays both short and “full-length”, meeting in groups not only to rehearse but to practice and develop theatrical crafts. None get paid. Some are even ready to part with fairly large sums for aforementioned workshops and seminars. All of them put in untold work hours and a lot of effort – after they get done with their day jobs. These are not “professionals”. Mostly, they don’t want to be. They have no interest in pursuing a theatrical career for a living. They just want to make theatre. In my article I explore what it is that people experience when participating in amateur theatre. The paper will mainly be based on a number of in depth interviews I conducted in 2009 and 2010 with people from the Selfoss Amateur Theatre Company, as well as my own experience of being a member of the same company for the last 25 years. Using analytical tools such as thematic analysis and Richard Schechner’s performance process as a time-space sequence I explore how making theatre creates communities and worlds and gives the participants freedom to let loose and play, if only for a time.